Noscapine Derivatives as New Chiral Catalysts in Asymmetric Synthesis: Highly Enantioselective Addition of Diethylzinc to Aldehydes - Mohebbi, Maryam; Bararjanian, Morteza; Ebrahimi, Samad N.; Smieško, Martin; Salehi, Peyman (Synthesis, 2018)
Noscapine, a natural alkaloid, has never been used as a parent scaffold in chiral induction. The first examples of noscapinoid compounds as efficient catalysts in asymmetric synthesis are now reported. Three derivatives of noscapine were synthesized from its reaction with different Grignard reagents. Asymmetric addition of diethylzinc to aldehydes was performed in the presence of these catalysts in high yields and good to excellent ees.
Keywords: noscapine; asymmetric reaction; diethylzinc; alkaloids; MacroModel